2011
DOI: 10.2165/11538930-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Honey and Wound Healing

Abstract: Honey has been used to treat wounds throughout the ages. This practice was rooted primarily in tradition and folklore until the late 19th century, when investigators began to characterize its biologic and clinical effects. This overview explores both historic and current insights into honey in its role in wound care. We describe the proposed antimicrobial, immunomodulatory, and physiologic mechanisms of action, and review the clinical evidence of the efficacy of honey in a variety of acute and chronic wound ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(76 citation statements)
references
References 51 publications
2
65
0
3
Order By: Relevance
“…Its beneficial properties as a wound-healing agent have been known and used since ancient times. Modern studies have confirmed the great potential of honey in healing of wounds and burns (reviewed in (34,26)). this potential is connected to the antibacterial properties of bee honey (35).…”
Section: Bulgarian Honeymentioning
confidence: 96%
“…Its beneficial properties as a wound-healing agent have been known and used since ancient times. Modern studies have confirmed the great potential of honey in healing of wounds and burns (reviewed in (34,26)). this potential is connected to the antibacterial properties of bee honey (35).…”
Section: Bulgarian Honeymentioning
confidence: 96%
“…27,28 In a recent review, it was demonstrated that honey could prevent cancerogenesis through alteration of cell cycle molecular processes 19 and some studies reviewed the effectiveness of honey for wound healing. 18,29,30 Although several studies demonstrated the soft tissue wound healing effect of honey, 18,23,29,30 its effect on bone defects has not been evaluated. Hence, the aim of the current study was to evaluate the effect of honey on healing of mandibular bone defects in a rat model.…”
Section: 5005/jp-journals-10024-2210mentioning
confidence: 99%
“…O mel de abelha ativa a reparação tecidual [15] e vem sendo utilizado na composição de medicamentos para o tratamento de diversos tipos de ferimentos, queimaduras de primeiro e segundo grau, úlceras, pé diabético, feridas infectadas, atuando como antimicrobiano natural e cicatrizante [16].…”
Section: Fgs Lima Et Al Scientia Plena 13 024601 (2017)unclassified